2008
DOI: 10.1111/j.1532-950x.2008.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy for Treatment of Unilateral Adrenocortical Carcinomas: Technique, Complications, and Results in Seven Dogs

Abstract: Objective-To investigate the feasibility of, and outcome after, laparoscopic adrenalectomy in dogs with unilateral adrenocortical carcinoma. Study Design-Case series. Animals-Dogs (n ¼ 7) with Cushing's syndrome caused by unilateral adrenocortical carcinoma. Methods-Laparoscopic adrenalectomy with the dog in lateral recumbency on the unaffected side. Three 5-mm portals (1 laparoscopic portal, 2 instrument portals) were placed in the paralumbar fossa. A fourth instrumental portal (5-12 mm) was placed above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 38 publications
5
78
1
2
Order By: Relevance
“…Biochemical analysis shows an increase in the levels of PA, ALT, triglycerides and cholesterol. Such changes are also reported by Peláez, Bouvy and Dupré (2008), Lang et al (2011) and Andrade et al (2014).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Biochemical analysis shows an increase in the levels of PA, ALT, triglycerides and cholesterol. Such changes are also reported by Peláez, Bouvy and Dupré (2008), Lang et al (2011) and Andrade et al (2014).…”
Section: Discussionsupporting
confidence: 55%
“…In imaging, as far as the side of the occurrence of the masses, Peláez et al (2008) Regarding the intraoperative complications, the most frequently observed is hypotension (LANG et al, 2011;MASSARI et al, 2011;BARRERA et al, 2013;ANDRADE et al, 2014). Three cases of hypotension were observed in this study, one of them along with bradycardia and compensatory ventricular escape.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, adrenalectomy has reported frequencies of intraoperative and postoperative complications of 15–50% of affected dogs, respectively. Perioperative mortality rate of adrenalectomy is high (5–29%)3, 4, 5, 6 and this could lead to unwillingness of the owner to accept the risk of this procedure. When surgery is not indicated or the owner declines surgery, medical management with the adrenocorticolytic drug mitotane has been recommended as an alternative treatment.…”
mentioning
confidence: 99%